Learning morphologically complex spoken words: Orthographic expectations of embedded stems are formed prior to print exposure - Beyersmann, E; Wegener, S; Nation, K; Prokupzcuk, A; Wang, H-C; Castles, A (American Psychological Association, 2021)
It is well known that information from spoken language is integrated into reading processes, but the nature of these links and how they are acquired is less well understood. Recent evidence has suggested that predictions about the written form of newly learned spoken words are already generated prior to print exposure. We extend this work to morphologically complex words and ask whether the information that is available in spoken words goes beyond the mappings between phonology and orthography. Adults were taught the oral form of a set of novel morphologically complex words (e.g., “neshing”, “neshed”, “neshes”), with a 2nd set serving as untrained items. Following oral training, participants saw the printed form of the novel word stems for the first time (e.g., nesh), embedded in sentences, and their eye movements were monitored. Half of the stems were allocated a predictable and half an unpredictable spelling. Reading times were shorter for orally trained than untrained stems and for stems with predictable rather than unpredictable spellings. Crucially, there was an interaction between spelling predictability and training. This suggests that orthographic expectations of embedded stems are formed during spoken word learning. Reading aloud and spelling tests complemented the eye movement data, and findings are discussed in the context of theories of reading acquisition.